Brain lipid binding protein (FABP7) as modulator of astrocyte function - Kipp, M; Clarner, T; Gingele, S; Pott, F; Amor, S; van der Valk, P; Beyer, C (Physiological research, 2011)
Over a century ago, hyperplasia and hypertrophy of astrocytes was noted as a histopathological hallmark of multiple sclerosis and was hypothesized to play an important role in the development and course of this disease. However until today, the factual contribution of astrocytes to multiple sclerosis is elusive. Astrocytes may play an active role during degeneration and demyelination by controlling local inflammation in the CNS, provoking damage of oligodendrocytes and axons, and glial scarring but might also be beneficial by creating a permissive environment for remyelination and oligodendrocyte precursor migration, proliferation, and differentiation. Recent findings from our lab suggest that brain lipid binding protein (FABP7) is implicated in the course of multiple sclerosis and the regulation of astrocyte function. The relevance of our findings and data from other groups are highlighted and discussed in this paper in the context of myelin repair.
Keywords: Disease Models, Animal; modely nemocí na zvířatech; Multiple Sclerosis; Nerve Tissue Proteins; myelinová pochva; signální transdukce; demyelinizační nemoci; proteiny vázající mastné kyseliny; lidé; Signal Transduction; Humans; nádorové supresorové proteiny; Fatty Acid-Binding Proteins; Animals; Tumor Suppressor Proteins; Cuprizone; zvířata; proteiny nervové tkáně; Carrier Proteins; FABP7; astrocyty; Astrocytes; roztroušená skleróza; Fatty Acid-Binding Protein 7; Demyelinating Diseases; transportní proteiny; kuprizon; Myelin Sheath